Implementasi Metode Eklektik dalam Pembelajaran Bahasa Arab di Pondok Pesantren Tahfidz Darul Falah Selangor - Malaysia - Siddiq, Wilda Fathimatuz Zahro'; Ratnaningtyas, Oktavia (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2025)
The successful foreign language teaching and learning process is one that successfully delivers students to an understanding and the ability to demonstrate the results of their language studies. Realizing students who are able to master the Four Maharah of Arabic only through formal classical learning is not enough. Likewise, Arabic must face different objective conditions between one country and another, between one institution and another, between one time period and another. Although accompanied by various existing field problems, with the right method, the intended effectiveness will not be impossible. Unfortunately, each method certainly has its own advantages and disadvantages, so the selection and combination of methods as a way to bridge these difficulties is the most solution to create a proportional and effective learning method. In his research, the researcher applied the thariqah intiqoiyyah method (combined method) with a choice of methods : thoriqoh al-qowaa’id wa at tarjamah (grammar and translation method) to fulfill Kitabah proficiency, thoriqoh sam’iyah syafawiyah (Audiolingual Method) to fulfill Istima’ proficiency, thoriqah al-qiraah (Reading Method) to fulfill Qira’ah proficiency, community language learning (Learning Language in Groups) to fulfill kalam proficiency. The results obtained are that Arabic language learning at Maahad Tahfiz Al-Quran Darul Falah Selangor Malaysia, with thariqah intiqoiyyah for heterogeneous students in one class with a variety of materials presented, has succeeded in delivering students to understanding and skills to demonstrate their learning outcomes representing each Al-mahaarat Al-lughowiyyah Al-arbi’ah (four Arabic language skills) well and correctly.